Modifikasi Perilaku Remaja dengan Pendekatan Belajar-melalui-Pengamatan dan Pengendalian Diri - Abdul Hadis (Universitas Negeri Malang, 2016)
Globalization era, characterized by a rapid growth in communication of information and transportation network all over the world, brings positive and negative effects. Those effects can be received by our adolescents or teenagers through sophisticated information media, either electronical media or printed media, and sophisticated transportation network as a consequence of the current growth of knowledge, technology, and arts. The adolescents have to be able to make their adjusments and dicisions properly. To do that, they can be prepared in applying the Observational Learning Modelling and Self Control Approach